Sympathectomy Ameliorates CFA-Induced Mechanical Allodynia via Modulating Phenotype of Macrophages in Sensory Ganglion in Mice - Mai L; Jia S; Liu Q; Chu Y; Liu J; Yang S; Huang F; Fan W (Dove Medical Press, 2022)
Lijia Mai,1,2,* Shilin Jia,1,2,* Qing Liu,3 Yanhao Chu,2 Jinyue Liu,2 Shengyan Yang,3 Fang Huang,1,2 Wenguo Fan1,2 1Hospital of Stomatology, Guanghua School of Stomatology, Sun Yat-sen University, Guangzhou, People's Republic of China; 2Institute of Stomatological Research, Sun Yat-sen University, Guangdong Provincial Key Laboratory of Stomatology, Guangzhou, People's Republic of China; 3Faculty of Dentistry, The University of Hong Kong, People's Republic of China*These authors contributed equally to this workCorrespondence: Wenguo Fan; Fang Huang, Guanghua School of Stomatology, Sun Yat-sen University, No. 74 Zhongshan Rd 2, Guangzhou, 510080, People's Republic of China, Tel +86 20 87330570, Fax +86 20 87330709, Email fanweng@mail.sysu.edu.cn; hfang@mail.sysu.edu.cnBackground: The sympathetic nervous system (SNS) is suggested to be involved in some forms of pain, but the mechanisms of which are incompletely known. Moreover, there is a lack of information on the regulatory role of the SNS on macrophages in sensory ganglion, which plays an important role in pain development. The present study aims to investigate the effects of the SNS on orofacial inflammatory pain and examine, if any, how the SNS influences trigeminal ganglion (TG) macrophage responses.Methods: Sympathectomy was performed on male C57BL/6 mice before receiving a local injection of Complete Freund's adjuvant (CFA) to induce inflammatory pain. Effects of sympathectomy on orofacial pain were examined by Von Frey test and c-Fos expression. Polarization of TG macrophage was evaluated by immunohistochemistry and the level of norepinephrine (NE) in the TG were determined by liquid chromatography. Sympathetic signaling to TG macrophages were predicted based on single-cell analysis.Results: CFA injection induced a significant increase in mechanical allodynia, the number of c-Fos-positive neuron, and the level of NE in TG, which were largely reduced by sympathectomy. The number of M1 macrophages was markedly increased by CFA and was largely reduced by sympathectomy from 1 to 14 days post-injection. Single-cell RNA sequencing analysis and immunofluorescence staining showed that TG macrophages mainly express β 2 adrenergic receptors for NE. Cell-cell communication analysis predicted sympathetic signaling that may modulate macrophage phenotypes, including Colony-stimulating factor-1, Migration inhibitory factor, Pleiotrophin and Nicotinamide phosphoribosyl transferase.Conclusion: The SNS may involve in CFA-induced mechanical allodynia via modulating macrophage phenotypes in the TG. Targeting sympathetic activation might be useful in treating some painful conditions in the orofacial region.Keywords: trigeminal ganglion, orofacial pain, sympathectomy, macrophages phenotype, neuroinflammation